The wideband signals in radio systems (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2007)
In the article the principles of formation wideband signals and construction of spread spectrum systems are esteemed. Are adduced of the main advantage of usage of such systems, and also the ways of formation and processing of wide-band signals are adduced.